Sex differences in the TLR-mediated response of pDCs to HIV-1 are associated with higher immune activation in infected women - Meier, Angela (2009)
Manifestations of viral infections can differ between women and men1, and significant sex differences have been described in the course of HIV-1 disease. HIV-1-infected women tend to have lower viral load levels early in HIV-1 infection, but progress faster to AIDS for a given viral load than men2–7. Here we demonstrate substantial sex differences in the response of plasmacytoid dendritic cells (pDCs) to HIV-1. pDCs derived from women produce significantly more interferon-α (IFN-α) in response to HIV-1-encoded TLR7 ligands than pDCs derived from men, resulting in stronger secondary activation of CD8+ T cells. In line with these in vitro studies, treatment-naïve chronically HIV-1-infected women had significantly higher levels of CD8+ T cell activation than men after adjusting for viral load. These data show that sex differences in TLR-mediated activation of pDCs can account for higher immune activation in women compared to men at a given HIV-1 viral load, and provide a mechanism by which the same level of viral replication might result in faster HIV-1 disease progression in women compared to men. Modulation of the TLR7 pathway in pDCs may therefore represent a novel approach to reduce HIV-1-associated pathology.